Acoustic properties of deformed rocks in the Nobeoka thrust, in the Shimanto Belt, Kyushu, Southwest Japan. (11th May 2017) - Hashimoto, Yoshitaka; Abe, Shogo; Tano, Hiroki; Hamahashi, Mari; Saito, Saneatsu; Kimura, Gaku; Yamaguchi, Asuka; Fukuchi, Rina; Kameda, Jun; Hamada, Yohei; Kitamura, Yujin; Fujimoto, Koichiro; et al.
Abstract: Laboratory measurements for compressional and shear wave velocities (Vp and Vs, respectively) and porosity were conducted with core samples from the Nobeoka Thrust Drilling Project (NOBELL) under controlled effective pressure (5–65 MPa at 5 MPa intervals) and wet conditions. Samples were classified according to deformation texture as phyllite, foliated cataclasite, or non‐foliated cataclasite. Measured values of Vp, Vs, and porosity are within a range of 5.17–5.57 km/s, 2.60–2.71 km/s, and 2.75–3.10 %, respectively, for phyllite; 4.89–5.23 km/s, 2.46–2.57 km/s, and 3.58–4.53 %, respectively, for foliated cataclasite; and 4.90–5.32 km/s, 2.51–2.63 km/s, and 3.79–4.60 %, respectively, for non‐foliated cataclasite, which are all consistent with the previous laboratory experiments conducted with outcrop samples under dry conditions. However, our results also indicate higher Vp and Vs and lower porosity than those measured by the previous studies that adopted the wire‐line logging methods. The variations in Vp, Vs, and porosity are controlled by deformation structure and are greater for phyllite and foliated cataclasite than for non‐foliated cataclasite. Abstract : Characteristic deformation textures of tested samples of (a) phyllite; (b) foliated cataclasite; and (c) non‐foliated cataclasite.